Hot corrosion of austenitic steel in Molten alkali sulphate deposits at 850°C - Mohammed Misbahul, Amin (Carl Hanser Verlag, 2009)
Link to publisher's homepage at http://www.materialography.de/PractMet/Archive/2008/index.php?id=g